BUILD CUSTOMERS LOYALTY PRODUCT LE MINERALE DISPOSABLE GALLONS IN PROBOLINGGO CITY - Muhammad Syarif Hidayatullah; Elmas Elmas (JPIM (Jurnal Penelitian Ilmu Manajemen), 2022)
This study aims to influence the effect of green marketing and brand image on customer loyalty of disposable gallon Le Minerale in Probolinggo City. This study uses quantitative methods with a sample of 100 respondents. Collecting data using questionnaires. Data analysis using analysis of Validity and Reliability Test, Classical Assumption Test (normality test, multicollinearity test, heteroscedasticity test, autocorrelation test. The results of the study show that partially green marketing has a positive and significant effect on customer loyalty Le Minerale Gallon disposables in Probolinggo City and brand image also has a positive and significant effect on customer loyalty of disposable Le Minerale Gallons in Probolinggo City.This study aims to influence the effect of green marketing and brand image on customer loyalty of disposable gallon Le Minerale in Probolinggo City. This study uses quantitative methods with a sample of 100 respondents. Collecting data using questionnaires. Data analysis using analysis of Validity and Reliability Test, Classical Assumption Test (normality test, multicollinearity test, heteroscedasticity test, autocorrelation test. The results of the study show that partially green marketing has a positive and significant effect on customer loyalty Le Minerale Gallon disposables in Probolinggo City and brand image also has a positive and significant effect on customer loyalty of disposable Le Minerale Gallons in Probolinggo City.